Work Stress, Work-Related Rumination, and Depressive Symptoms in University Teachers: Buffering Effect of Self-Compassion - Wu Q; Cao H; Du H (Psychology Research and Behavior Management, 2023)
Qinglu Wu,1 Hongjian Cao,2– 4 Hongfei Du1 1Institute of Advanced Studies in Humanities and Social Sciences, Beijing Normal University, Zhuhai, People’s Republic of China; 2Applied Psychology Program, School of Humanities and Social Science, The Chinese University of Hong Kong (Shenzhen), Shenzhen, People’s Republic of China; 3Department of Psychology, The University of Hong Kong, Hong Kong, People’s Republic of China; 4Department of Human Development & Family Science, Florida State University, Tallahassee, FL, USACorrespondence: Qinglu Wu, Email qinglu-wu@hotmail.comPurpose: The association between work stress and depressive symptoms has been well documented. More research is still needed to further investigate the underlying explanatory process mechanism and the potential protective function of personal resource in attenuating the negative effect of work stress on mental health. To address this gap and informed by the stress process model and emotion regulation theory,the present study examined the indirect role of work-related rumination and the buffering effect of self-compassion in university teachers, a population with increased vulnerabilities for both work stress and mental health issues.Methods: This study collected data from 727 university teachers (Mage = 37.65 ± 7.77 years, 61.5% women) through an online survey. Indirect effect analysis and moderation effect analysis were implemented using structural equation modeling via Mplus.Results: Work stress was directly and indirectly associated with depressive symptoms through work-related rumination, and self-compassion moderated the associations between (a) work stress and depressive symptoms and (b) work-related rumination and depressive symptoms. The direct and indirect effects of work stress on depressive symptoms were weaker in university teachers with high levels of self-compassion than in those with low levels of self-compassion.Conclusion: Work stress was associated with depressive symptoms through a cognitive pathway. The findings deepen our understanding of the link between work stress and mental health outcomes by revealing the indirect role of cognitive processes, the protective function of emotion regulation strategies, and their interplay. Reducing work-related rumination and strengthening self-compassion may constitute effective interventions to alleviate the negative effects of work stress on mental health.Keywords: work stress, work-related rumination, self-compassion, depressive symptoms, university teachers